2002
DOI: 10.1038/sj.onc.1205192
|View full text |Cite|
|
Sign up to set email alerts
|

The putative tumor suppressor RASSF1A homodimerizes and heterodimerizes with the Ras-GTP binding protein Nore1

Abstract: Nore and RASSF1A are noncatalytic proteins that share 50% identity over their carboxyterminal 300 AA, a segment that encompasses a putative Ras-Rap association (RA) domain. RASSF1 is expressed as several splice variants, each of which contain an RA domain, however the 340 AA RASSF1A, but not the shorter RASSF1C variant, is a putative tumor suppressor. Nore binds to Ras and several Ras-like GTPases in a GTP dependent fashion however neither RASSF1 (A or C) or the C. elegans Nore/RASSF1 homolog, T24F1.3 exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
207
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(212 citation statements)
references
References 38 publications
(31 reference statements)
4
207
1
Order By: Relevance
“…For several RASSF members growth suppression is enhanced by co-transfection of constitutively active Ras proteins (Vos et al, 2000(Vos et al, , 2003a or by artificially forcing membrane localization thereby facilitating interaction with Ras (Eckfeld et al, 2004). Co-immunoprecipitation experiments show that RASSF proteins bind several Ras superfamily members as Ras-guanosine triphosphate (GTP) but not Ras-GDP and that this interaction occurs between the RA domain and the effector domain of Ras proteins (Vavvas et al, 1998;Vos et al, 2000Vos et al, , 2003aKhokhlatchev et al, 2002;Ortiz-Vega et al, 2002;Eckfeld et al, 2004). In the case of RASSF1A association with Ras may occur indirectly through heterodimerization with NORE1A or the scaffold protein CNK1 (Ortiz-Vega et al, 2002;Rabizadeh et al, 2004).…”
Section: Rassf1mentioning
confidence: 99%
See 1 more Smart Citation
“…For several RASSF members growth suppression is enhanced by co-transfection of constitutively active Ras proteins (Vos et al, 2000(Vos et al, , 2003a or by artificially forcing membrane localization thereby facilitating interaction with Ras (Eckfeld et al, 2004). Co-immunoprecipitation experiments show that RASSF proteins bind several Ras superfamily members as Ras-guanosine triphosphate (GTP) but not Ras-GDP and that this interaction occurs between the RA domain and the effector domain of Ras proteins (Vavvas et al, 1998;Vos et al, 2000Vos et al, , 2003aKhokhlatchev et al, 2002;Ortiz-Vega et al, 2002;Eckfeld et al, 2004). In the case of RASSF1A association with Ras may occur indirectly through heterodimerization with NORE1A or the scaffold protein CNK1 (Ortiz-Vega et al, 2002;Rabizadeh et al, 2004).…”
Section: Rassf1mentioning
confidence: 99%
“…Co-immunoprecipitation experiments show that RASSF proteins bind several Ras superfamily members as Ras-guanosine triphosphate (GTP) but not Ras-GDP and that this interaction occurs between the RA domain and the effector domain of Ras proteins (Vavvas et al, 1998;Vos et al, 2000Vos et al, , 2003aKhokhlatchev et al, 2002;Ortiz-Vega et al, 2002;Eckfeld et al, 2004). In the case of RASSF1A association with Ras may occur indirectly through heterodimerization with NORE1A or the scaffold protein CNK1 (Ortiz-Vega et al, 2002;Rabizadeh et al, 2004). Taken together these data indicate the RASSF family of proteins are genuine Ras effectors that mediate some of the growth inhibitory functions of Ras proteins.…”
Section: Rassf1mentioning
confidence: 99%
“…The homology of RASSF1A with the mammalian Ras effector novel Ras effector (NORE)1 suggests that the RASSF1A gene product may function in signal transduction pathways involving Ras-like proteins. However, recent data indicate that RASSF1A itself binds to RAS only weakly and that binding to RAS may require heterodimerization of RASSF1A and NORE1 (Ortiz-Vega et al, 2002). In addition, there is evidence for an association of both NORE1 and RASSF1A with the pro-apoptotic kinase MST1 and that this interaction is involved in apoptosis induced by activated Ras .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that RASSF1 binds Ras in a GTP-dependent manner and that its overexpression induces apoptosis (Vos et al, 2000). Our recent data indicate that the pro-apoptotic effect of RASSF1 may require heterodimerization with NORE1 and that RASSF1 itself binds to Ras only very weakly (Ortiz-Vega et al, 2002). In addition, there is evidence for an association of both NORE1 and RASSF1 with the pro-apoptotic kinase MST1, and that this interaction is involved in apoptosis induced by activated Ras .…”
mentioning
confidence: 97%